Turkey trouble on the National Mall - Roy, Ron, 1940- (Roy, Ron, 1940- Capital mysteries, 2012)
"KC and Marshall convince the President of the United States to pardon more than one turkey for Thanksgiving, but all 117 of them are stolen off the National Mall"--